Small and Medium Enterprise Debt Decision: A Best-Worst Method Framework - Brajaballav Kar; Biswajit Mohapatra; Satyaballav Kar; Sushanta Tripathy (Operational Research in Engineering Sciences: Theory and Applications, 2022)
Lack of resources among small and medium enterprises (SMEs) but a lower level of debt, despite policy incentives, is perplexing. The level of debt in SMEs has four influencers such as the business owner, firm, bank, and government. Primarily, business owners would like to increase wealth and retain control, banks would lend and cover the risk of debt, and the government would promote SMEs for employment and growth. Thus, the decision for debt and subsequent growth and performance appears simple. But, the Reserve of Bank of India observes that the level of debt in SMEs remains below the expected level, over the years, despite policy incentives. Though the factors leading to debt decisions are known, how the priorities of such factors explain the contradiction are lacking. This research identifies various factors leading to debt decisions from the literature, uses the Best Worst Methodology (BWM) to find their relative importance, and corroborates it with the qualitative data gathered from experts. We find that banks at 34 percent weight in debt decision (highest), 6 percent more compared to the firm. The government has the least importance, at around 10 percent. However, the firm performance, trust in the bank, compliance, firm growth, and bank-firm relationship are the top five decision variables for debt. Given the stronghold of banks, their actions and decision-making must be suitable for the SME business context. Operationalization of the qualitative criteria of bank’s trust in SME, digitalization, improvement in bank transaction documentation, and the possibility of digital gateway organizations emerging as institutional SME lenders are some future research scopes.